Comparative Analysis of Huffman Coding Implementations for Efficient Data Communication Using Greedy and Divide-and-Conquer Techniques - Frye, Kaleb; Ronhovde, Josh; Stonestreet, Connor; Fazea, Yousef (Yayasan Asmin Intelektual Berkah, 2024)
Efficient data compression techniques are required to minimize storage and processing overhead due to modern systems' growing amount of data. Huffman Coding is a lossless compression technique that maintains data integrity by assigning shorter bit codes to characters appearing frequently, reducing size. Our analysis focuses on two implementation methodologies: greedy technique and divide and conquer. To find efficient solutions, divide-and-conquer algorithms partition problems into smaller components. In contrast, greedy algorithms strive to attain the utmost attainable result at each level. Our extensive investigation centers on the timing and space intricacies of diverse methodologies, enabling a comparative analysis that underscores their respective merits and drawbacks.